2015
DOI: 10.3390/v7052450
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the DNA Damage Response throughout the Papillomavirus Life Cycle

Abstract: The DNA damage response (DDR) maintains genomic integrity through an elaborate network of signaling pathways that sense DNA damage and recruit effector factors to repair damaged DNA. DDR signaling pathways are usurped and manipulated by the replication programs of many viruses. Here, we review the papillomavirus (PV) life cycle, highlighting current knowledge of how PVs recruit and engage the DDR to facilitate productive infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 120 publications
0
63
0
5
Order By: Relevance
“…Once entered the nucleus, HPV replicates to a low copy number (10–200 copy number/cell) during the initial amplification and establishment of infection [23]. As the proliferating cells (harboring HPV genomes) undergo transition through differentiation, the mode of viral genome replication switches to support productive viral genome amplification concomitant with increased levels of the E1 and E2 replication proteins [24]. In the terminally differentiated layer of epithelium L1 and L2 capsid proteins are expressed and viral particles are assembled.…”
Section: Entry Of Hpv and Life Cycle In Cervical Epithelial Cellmentioning
confidence: 99%
“…Once entered the nucleus, HPV replicates to a low copy number (10–200 copy number/cell) during the initial amplification and establishment of infection [23]. As the proliferating cells (harboring HPV genomes) undergo transition through differentiation, the mode of viral genome replication switches to support productive viral genome amplification concomitant with increased levels of the E1 and E2 replication proteins [24]. In the terminally differentiated layer of epithelium L1 and L2 capsid proteins are expressed and viral particles are assembled.…”
Section: Entry Of Hpv and Life Cycle In Cervical Epithelial Cellmentioning
confidence: 99%
“…The importance of the DNA damage response (DDR) to HPV replication is becoming increasingly clear (McKinney et al, 2015). Previous studies identified a role for the DDR kinase ATM (Ataxia Telangiectasia-Mutated) in productive replication of HPV31 (Moody and Laimins, 2009), which may facilitate viral DNA synthesis, at least in part, through the recruitment of DNA repair factors to viral replication centers (Chappell et al, 2015; Gillespie et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In response to DNA damage, Chk1 is rapidly activated, transduces the checkpoint signal, and finally facilitates cell cycle arrest and DDR [37,38]. Recent studies have shown that HPVs utilized DDR machinery to facilitate productive viral replication [11,39,40]. The level of phosphorylated Chk1 was enhanced and sustained in HPV16 E6-expressing fibroblasts [41].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the importance of the cellular DNA damage response (DDR) to the viral replication is becoming increasing clear [11][12][13]. The act of DDR requires the activation of 4 protein kinases that form canonical ATM-Chk2 and ATR-Chk1 pathway [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%